2010
DOI: 10.1080/14631371003740738
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of government-sponsored programmes in supporting the SME sector in Poland

Abstract: The objective of this article is to provide a comprehensive evaluation of the government assistance programmes to small and medium-size enterprises (SMEs) in Poland and to assess the effectiveness of these programmes in stimulating development of the SME sector. There are three main conclusions from the study. First, the Polish government support programmes are poorly structured, fragmented and untargeted. Second, the programmes do not meet the actual needs of the sector and, hence, are poorly used. Third, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
9

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 10 publications
0
15
0
9
Order By: Relevance
“…However, Klonowski (2010) examined the government supported programs for SME development in Poland and revealed that government support was not efficient. It was also found that entrepreneurs were not well informed about the grant projects and hence, lot of entrepreneurs suffered from lack of credit.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, Klonowski (2010) examined the government supported programs for SME development in Poland and revealed that government support was not efficient. It was also found that entrepreneurs were not well informed about the grant projects and hence, lot of entrepreneurs suffered from lack of credit.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…a nyugati programok tapasztalata szerint ez utóbbi befektetői kör miatt a hibrid alapok sikeres működésének különösen fontos feltétele a helyi hálózatok, a helyi viszonyok ismerete, a helyi befektetőkkel való kapcsolat megléte, ami elengedhetetlen a befektetési lehetőségek közötti megfelelő válasz-táshoz (Tillväxtverket [2011]). a hibrid kockázatitőke-alapok befektetők közötti választási lehetőségeinek a régióban azonban korlátokat szabott, hogy a térségben viszonylag kevés kisebb méretű vagyonkezelő intézmény, valamint üzleti angyal található (Szerb és szerzőtársai [2007], Karsai [2012], Klonowski [2010], [2012]). Kevés a családi vagyonkezelő, befektethető szabad vagyonnal rendelkező alapítvány, illetve korlátozott a rendszeres befektetésekre vál-lalkozó üzleti angyalok száma, így a kelet-közép-európai térség hibrid kockázatitőke-alapjaiban jellemzően gazdag magánszemélyek vehettek részt.…”
Section: Az áLlami Tőkeprogramok Nem áLlami Befektetőiunclassified
“…The fi ndings of several survey studies suggest that the impact of external support to SMEs is rather limited (eg, Bennett and Robson, 1999;Crick, 1997;Klonowski, 2010;Kösters and Obschonka, 2011;Mahajar and Yunus, 2006;Moini, 1998;Robson and Bennett, 2000;Wren and Storey, 2002). Other studies do provide evidence in support of government assistance to SMEs (eg, Belso Martínez, 2010;Gongora et al, 2010;Marshall et al, 1993;Mole et al, 2009).…”
Section: Literature Review and Institutional Backgroundmentioning
confidence: 91%